The 'Relevant' Stability of Proteins with Equilibrium Intermediates. (2002) - Sancho, Javier; Bueno, Marta; Campos, Luis A.; Fernandez-Recio, Juan; Iran, Maria Pilar; Lopez, Jon; Machicado, Claudio; Pedroso, Idolka; Toja, Miguel
Abstract : Proteins perform many useful molecular tasks, and their biotechnological use continues to increase. As protein activity requires a stable native conformation, protein stabilisation is a major scientific and practical issue. Towards that end, many successful protein stabilisation strategies have been devised in recent years. In most cases, model proteins with a two-state folding equilibrium have been used to study and demonstrate protein stabilisation. Many proteins, however, display more complex folding equilibria where stable intermediates accumulate. Stabilising these proteins requires specifically stabilising the native state relative to the intermediates, as these are expected to lack activity. Here we discuss how to investigate the 'relevant' stability of proteins with equilibrium intermediates and propose a way to dissect the contribution of side chain interactions to the overall stability into the 'relevant' and 'nonrelevant' terms. Examples of this analysis performed on apoflavodoxin and in a single-chain mini antibody are presented.